2021
DOI: 10.1039/d1cy00419k
|View full text |Cite
|
Sign up to set email alerts
|

First-principles-informed energy span and microkinetic analysis of ethanol catalytic conversion to 1,3-butadiene on MgO

Abstract: Kinetic modeling of single-step catalytic conversion of ethanol to 1,3-butadiene is necessary to inform accurate process design. This paper uses first-principles-informed energy span and microkinetic analysis to explore the reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The differential equations describing the surface kinetics were solved using the Python Catalysis Kinetics (PyCatKin) tool, 54 using the SciPy 55 lsoda wrapper to the Fortran ODEPACK library, 56 and backward differentiation formulas. The relative and absolute tolerances were set to 1 × 10 −8 and 1 × 10 −10 , respectively.…”
Section: S S Smentioning
confidence: 99%
“…The differential equations describing the surface kinetics were solved using the Python Catalysis Kinetics (PyCatKin) tool, 54 using the SciPy 55 lsoda wrapper to the Fortran ODEPACK library, 56 and backward differentiation formulas. The relative and absolute tolerances were set to 1 × 10 −8 and 1 × 10 −10 , respectively.…”
Section: S S Smentioning
confidence: 99%
“…The dopant metals, such as Na and Zn, help in the dehydrogenation reaction of ethanol to relative products such as acetaldehyde, and Zr helps in or supports the catalyzation of aldol condensation to produce 1,3-butadiene. Some papers demonstrated that the adequate loading of MgO on ZrO 2 could aid in a two-stage process of producing 1,3-butadiene from ethanol dehydration [1,[7][8][9][10]. To avoid the low yield and productivity of 1,3-butadiene from ethanol, ash, Mg, and Zr, catalysts are used in a fixed bed or dual fixed bed reactor, as the catalyst had different metal constituents and would provide enough support for different metal-supported catalysts.…”
Section: Introductionmentioning
confidence: 99%